Research on the Application of Advocacy-Motivation Theory in Tobacco Control Activities in Universities (The Journal of Medicine, Humanity and Media, 2025)
Objective: To evaluate the effectiveness of campus tobacco control activities based on advocacy-motivation theory and explore effective strategies for university tobacco control education.Methods: A cross-sectional intercept survey was conducted during a World No Tobacco Day campaign at a university in Beijing. Data were analyzed using SPSS 21.0 software.Results: At the cognitive level, participants’ awareness of smoking-related risks (stroke, heart disease, impotence, and blindness) significantly increased after the activity (P
Keywords: Advocacy-Motivation Theory; Tobacco Control; Risk Awareness; University Students; Health Communication